Advertising – a Necessary “Elixir of Life” for Capitalism: On the Critique of the Political Economy of Advertising - Manfred Knoche (tripleC: Communication, Capitalism & Critique. Open Access Journal for a Global Sustainable Information Society, 2023)
This contribution aims to lift the ideological veil of apologetics and pseudo-criticism on advertising with the help of a reality-based systematic analysis that contributes to a materialistic theory of advertising. The content-related and methodological basis of such a theory is a Critique of the Political Economy of Advertising oriented towards the critique of capitalism and academic knowledge originally presented by Karl Marx and current societal analyses based on it. In this context, the academic objective is to consider the economic, political, and societal functions of (media) advertising. In doing so, the elementary economic and ideological functions of advertising for the existence and further development of the market economy and capitalist economic and societal systems become recognisable. Advertising then no longer appears as a necessary evil but as a necessary "elixir of life” for the media industry, the economy, and capitalism as a whole. Based on the applied critical political-economic analysis, it becomes clear that on the level of capitalism as an economic and societal system, advertising thus contributes economically and ideologically to the stabilisation of the systemic foundations of capitalist societies (the capital-labour relationship, the regime of accumulation; the economic, societal, and political [advertising] functions of the media). It is shown that a Critique of the Political Economy of Advertising – especially from the point of view of the necessarily growing importance of advertising for media production – also contributes to the development of a Critique of the Political Economy of the Media.
Keywords: 330; advertising; Werbung; Kritik der politischen Ökonomie der Medien; Critique of the Political Economy of the Media